The cooling phase of Type I X-ray bursts observed with RXTE in 4U 1820-30 does not follow the canonical F-T^4 relation - García, Federico (2013)
We analysed the complete set of bursts from the neutron star low-mass X-ray binary 4U 1820-30 detected with the Rossi X-ray Timing Explorer (RXTE). We found that all are photospheric radius expansion bursts, and have similar duration, peak flux and fluence. From the analysis of time-resolved spectra during the cooling phase of the bursts, we found that the relation between the bolometric flux and the temperature is very different from the canonical F-T^4 relation which is expected if the apparent emitting area on the surface of the neutron star remains constant. The flux-temperature relation can be fitted using a broken power law, with indices v1 = 2.0 +/- 0.3 and v2 = 5.72 +/- 0.06. The departure from the F-T^4 relation during the cooling phase of the X-ray bursts in 4U 1820-30 could be due to changes in the emitting area of the neutron star while the atmosphere cools down, variations in the colour-correction factor due to chemical evolution, or the presence of a source of heat, e.g. residual hydrogen nuclear burning, playing an important role when the burst emission ceases.